Is Systems Engineering Effectiveness the Heart of Today's Employability Skills?. Issue 3 (10th October 2022) - Hutchison, Nicole; McDermott, Tom
ABSTRACT: There are three essential and interrelated sets of personal characteristics and skills that are acquired by the most valued and effective individuals as they develop their careers. These are (1) self‐leadership and learning, (2) complex problem solving, and (3) team leadership and collaboration . These are interdependent and develop iteratively through practice in authentic work‐related contexts. They are at the heart of the Helix study which was conducted by the Systems Engineering Research Center to discover the sets of proficiencies that make a systems engineer effective in their roles (Hutchison and Verma 2018). They are also at the heart of the "employability skills" so desired by today's businesses. Each of these three skillsets is supported by tools of different types and can be embedded into education and organizational learning programs. In this article we relate the development of effective systems engineers as a model for all professionals and frame a set of learning objectives that individuals and organizations can use to accelerate desired employability skills.